Measurement of a side-wall boundary effect in soil columns using fibre-optics sensing. Issue 4 (December 2001) - Sentenac, P.; Lynch, R.J.; Bolton, M.D.
Abstract : Side-wall leakage - the preferential flow of water or pollutants near the wall of a soil column - has been studied using in-situ fibre-optical detection of a dye solution at the boundary and in the centre of a soil column. A difference in flow velocity was clearly observed between centre and column wall boundary for different surfaces. The velocity differenceis modified by sand-coating of the wall surface.